Development and validation of short amplicon-length PCR assays for the detection of feline species in processed foods / Md. Al Amin - Md. Al Amin, - (2015)
Food falsification is a common concern, but has been mutually practiced in the meat industry, especially for processing food products, for realizing an extra profit. The everyday happenings such horse, porcine, rat and dog meats forgeries in various foods have made consumers increasingly worried to safeguard their religious faith, health, money and wildlife in natural habitats. The consumers of the Halal food market have reached to 1.8 billion and turnover has crossed US Dollar 700 billion in 2012 and it has been projected to reach at US$ 1.6 trillion by the 2030. Since the market is quite large and opportunities in halal food business are huge, it has been targeted for adulteration for a long time. Consumption or mixing of feline ingredients in halal and kosher foods is forbidden and various diseases such as SARS, anthrax and hepatitis could be transmitted through feline meats. However, since feline species are abundant across the world without market price and their meats are consumed in exotic foods, the chances of their adulteration in common meats are very high. For meat specification, DNA-based techniques are preferred over protein and lipid-based molecular identification schemes since DNA biomarkers, especially the short-length one, is extremely stable even under harsh processing condition (heat, pressure and additives chemicals) and compromised states (natural decomposition) where most protein-based markers are denatured or degraded. Although several PCR assays have been proposed for feline species detection, those assays are based on longer length target amplicon which are assumed to break down under food processing treatments. Thus, a reliable detection of feline ingredients is crucial for the safety of consumer health, religious faith and fair-trade economy. In this study, a 69-bp target of feline mitochondrial cytochrome b gene was selectively amplified using a pair of primers of the said species. The assay was specific for feline species under raw, processed, admixed and commercial food matrices. The specificity of the developed assay was checked against commercially important 14 terrestrial 5 aquatic and 5 plants species. The target DNA stability under various food processing conditions such boiling, autoclaving and microwaving that degrade DNA and exceptional constancy were found in all treatments. The lower limit of detection of the assay was reflected by its ability to detect 0.1 pg of feline DNA from raw meats, 0.01% (w/w) in different admixes and 0.1% (w/w) of feline meats in burger as well as meatball formulations, respectively. The PCR product was further authenticated by restriction digestion followed by RFLP analysis in microfluidic-based lab-on a chip system. Theoretical analysis revealed two RFLP fragments of length 43 and 26-bp which will be separated using a highly sensitive microfluidic-based lab-on a chip system with a resolution of ≤10-bp. Very short amplicon-length, extreme stability and high sensitivity suggested that this assay could be used by the regulatory bodies for the routine assessments of feline species in food forensics or archaeological investigations. Therefore, a short amplicon-length polymerase chain reaction (PCR) was developed and validated it by restriction fragment length polymorphism (RFLP) analysis for the authentication of feline meat in processed foods.